Жил-был такс: [повесть] / Елена Арифуллина ; [художник К. Скоморохова] - Арифуллина Елена Юрьевна (Серия "Тузик, Мурзик и другие", 2016)
Экземпляры: аб. (20241008) / Инвентарный номер: 65264 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 81 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44